PENGARUH BLENDED LEARNING TERHADAP KUALITAS PEMBELAJARAN PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MIN 2 BREBES - Rochim, Ahmad Abdul (Jurnal Ilmiah Multidisipin, 2024)
The purpose of this study was to determine the effect of the blended learning model on the quality of Islamic cultural history learning at MIN 2 Brebes. The method used in this study is quantitative, namely through Validity Test, Reliability, Normality, Linearity, Hypothesis Testing, Coefficient of Determination and Simple Linear Regression using the SPSS application. There were 122 samples taken through the Non-Probability Sampling Technique, namely Purposive Sampling. The research instrument uses a questionnaire distributed using the Google Form application. Then the results are obtained from the calculation of Simple Linear Regression of 0.000 <0.05 provided that the significance value is <0.05. So it can be concluded that the two variables of blended learning and the quality of Islamic cultural history learning influence each other. So a determination correlation of 0.473 is obtained and the interpretation is said to have a sufficient correlation. Thus testing the H1 hypothesis is accepted that blended learning has an influence on the quality of Islamic cultural history learning.